Ablation of Hepatic Tumors through the Use of a Novel Magnetic Nanocomposite Probe: Magnetic Characterization and Finite Element Method Analysis. (3rd March 2019) - Konku, Yvonne; Kutor, John; Yaya, Abu; Kan-Dapaah, Kwabena
Abstract : The authors recently proposed a novel system for thermoablation—based on nanoheating—that can potentially overcome limitations associated with previously reported techniques. The aim of this study was to evaluate the therapeutic performance of the system in the ablation of hepatic tissue, the most frequently ablated. A model nanocomposite system, maghemite nanoparticle-filled polydimethylsiloxane, was prepared, and its magnetic properties were studied as a function of nanoparticle concentration. On the basis of measured magnetic properties, a 3D finite element method (FEM) model was used to explore the development of temperature and thermal damage in nonperfused and fully perfused tissue using alternating magnetic field (AMF) parameters that are acceptable for human use. The FEM model was tested for its validity using an analytical model. The saturation magnetization increased to about 9% of the value of pure maghemite nanoparticles over the range of volume fraction (vol. %) between 1 and 5%. Lesion sizes were shown to be greatly affected by tissue perfusion and time. FEM predictions showed good agreement with results obtained with an analytical model to within 7%. Probes fabricated with magnetic nanocomposite can potentially be used to achieve reasonable lesion sizes in hepatic tissues using human-safe AMF parameters.